ON THE EFFECTIVENESS OF THE PERIODEZATION OF MEMBERS OF THE PEOPLE’S REPRESENTATIVE COUNCIL IN TERMS OF JURIDICAL: EFEKTIVITAS PERIODESASI ANGGOTA DEWAN PERWAKILAN RAKYAT DALAM HUKUM - Agus Setiawan; Siti Khoiriah; Chandra Perbawati (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
Indonesian Legislative Assembly is the high institutions and public representatives with the authority to design, discuss and establish a law that the state requires. As in Article 7 Verse (4) Act number 13 in 2019 on MD3 that the term of parliament was five (5) years and ended when new members of the parliament were taking an oath. There is a legal vacuum to the effectiveness of the legislative regulatory management, which needs to be examined for whether or not there is a fight on the principle of certainty of law and democracy. To find answers to questions of formulated problems treated using normative law research with a descriptive approach with secondary data. The result of this study has been decided that the effectiveness of the regional autonomy and policy on micro finance as well as law.